Pyrrolidine‐Based P, O Ligands from Carbohydrates: Easily Accessible and Modular Ligands for the Ir‐Catalyzed Asymmetric Hydrogenation of Minimally Functionalized Olefins. Issue 23 (28th November 2018) - Elías‐Rodríguez, Pilar; Borràs, Carlota; Carmona, Ana T.; Faiges, Jorge; Robina, Inmaculada; Pàmies, Oscar; Diéguez, Montserrat
Abstract: The potential of P, O‐iminosugar based ligands in the Ir‐catalyzed asymmetric hydrogenation of minimally functionalized olefins is presented. These new ligands were prepared from easily available carbohydrates (D‐mannose, D‐ribose and D‐arabinose). The stereochemical and polyfunctional diversity of carbohydrates allowed the modulation of the ligands, both from their electronic properties and the rigidity of their backbone. High enantioselectivities ( ee 's up to 99 %) can be reached in the hydrogenation of selected tri‐ and disubstituted substrates. Abstract : Form follows functionality ! The potential of P, O‐iminosugar based ligands in the Ir‐catalyzed asymmetric hydrogenation of minimally functionalized olefins is presented. Improving previous results, the authors have demonstrated that the use of a more‐rigid bicyclic backbone not only positively affected the enantioselectivity but also extended the range of substrates that can be efficiently reduced.